A Single-Center Experience with an Intensivist-Led Brain-Dead Donor Management Program - Park, Jin (Ann Transplant, 2018)
BACKGROUND: The aim of this study is to report our experience of brain-dead donor management by a dedicated intensivist who had wide experience in treatment of hemodynamically unstable patient and to suggest a role for intensivists in organ donation. MATERIAL/METHODS: The management of brain-dead donors was performed by experienced intensivists. The hospital medical records and data from the Korean Network of Organ Sharing from August 2013 to December 2016 were reviewed retrospectively. RESULTS: Fifty-four brain death patients (3.2% of KONOS nationwide data) donated organs in our institution during 41 months. Dedicated intensivists managed deceased patients for the whole duration (2.81±1.21 days) of management, not only with conservative therapies like fluid resuscitation, vasopressor, or hormonal replacement, but also with pulmonary artery catheter insertion for cardiac output monitoring (n=47, 87.0%) and continuous renal replacement therapy (n=22, 40.7%). The number of donors increased each year. The mean number of retrieved organs in each deceased donor was 3.98±1.55, more than the national average (3.26) and comparable to the higher level among the recent worldwide data. The number of donations by organ was: 23 hearts (4.9% of nationwide data), 17 lungs (7.5% of nationwide data), 102 kidneys (3.3% of nationwide data), 47 livers (3.1% of nationwide data), 6 pancreases (2.9% of nationwide data), 1 pancreatic duct (11.1% of nationwide data), and 1 small intestine (12.5% of nationwide data). CONCLUSIONS: Management by dedicated intensivists will improve not only the number of actual organ donors, but also the number of harvested organs.